Моделирование возбуждения широкополосной щелевой антенны (теория и эксперимент) - Дорошенко, В. А.; Стрельницкий, А. А.; Стрельницкий, А. Е. (ХНУРЭ, 2014)
The results of theoretical and experimental studies of the model problem of excitation of a conical antenna with a slot cut along its ruling from the cone tip are presented. The theoretical results for the spatial field distribution by virtue of the derived rigorous solution of the boundary electromagnetic problem for a cone with a longitudinal slot are obtained. The experimental results of measurements of the cone antenna radiation pattern are given.
Keywords: conical antenna; rigorous solution